Red in the corpus of contemporary American English interpretation of color in law and politics section - Prihantoro Prihantoro (Jurnal Linguistik Terapan, 2014)
Color does not only correspond to light-spectrum-based visual identification of a concrete entity, but it may also symbolize abstract values conceived in a socio-cultural community. Some values are shared, but some others are distinctive. Even in one community, the meaning of a color might be multi-interpretable. For instance, the color of RED is understood as a ‘stop’ command when it comes on traffic light. However, in the compounds such as ‘red specialist’, ‘red herring’, or ‘red army’, we cannot take for granted that the <red> also means ‘stop’. Both linguistic and metalinguistic awareness are required to define what RED means. This paper seeks to describe the literal and non-literal meaning of RED in the Corpus of Contemporary American English (COCA), by focusing on laws and politic section. By using Keyword(s) in Context (KWIC) method, I have managed to retrieve 328 concordance lines where RED collocates with other token(s). I extracted the lines, including the extended context, for in depth interpretation. Both literal and non-literal meanings of the collocations are categorized into different classes, and the investigation indicates that in laws and politic science text, RED is a color that is often used to address negative polarities such as fallacy and ethnic discrimination.